PROPINQUITY OF AVARICIOUSNESS WITH IMPULSE BUYING TENDENCY - Shivang Dwivedi, Ramesh Kumar Chaturvedi (International Journal of Advanced Science and Technology, 2020)
Impulse buying behavior is a sudden spontaneous urge of the consumer to make unplanned purchaseafter seeing the product in the retail space. Such type of behavior involves purchasing without muchthinking. A number of studies have been conducted in the past regarding consumer decision making. Thisstudy has its base in the form of price sensitive impulse buyers. Though impulse buying behaviors hasbeen studied in past, little evidence is available in literature on segmenting impulse buyer market; neitherany specific scale has been developedto segment personalities based their impulse buyingtendencies.Different personality traits from perspective of retail consumers are discussed and it isanalyzed that how impulse buying market can be segmented based on the personalities of consumers.Using the technique of K means clustering analysis three segments are identified within impulse buyingmarket having distinctive characteristics, among them avaricious value seeking impulse buyers segmentdominates.Indian economy is a mixed economy and the Indian consumers generally tend to look forpurchasing whenever the prices are low or at least the prices are fair which is eventually visible in thisstudy also. This research will open insights about the segmenting impulse buyers to enable storemanagers enhance value per customer.